ANALISIS ELEMEN VISUAL PENERAPAN LETTER SPACING PADA KAMPANYE ANTI RASISME LIGA INGGRIS - Yosef Yulius; Nyoman Dewi Pebryani; Suharto Suharto; Amelia Aiununnisa; Hadhira Rahma (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The problem of racism can occur anywhere and anytime, including in the Premier League. With so many clubs and fans around the world, the Premier League is prone to racism from players, spectators, to fanatical fans. To minimize racism, the English League held an anti-racism campaign with the theme 'No Room For Racism' which used attractive typography visuals and meeting fonts that were rarely used. The purpose of this study is to analyze visual elements to assess the effectiveness of the visual use of typography in the 'No Room For Racism' campaign from the perspective of visual communication design. This study uses a qualitative descriptive method with data collection techniques, documentation, and analysis through aesthetic theory and semiotics. The results of the study show that the visual form of the logo of the